Patients' perspectives on self-testing of oral anticoagulation therapy: Content analysis of patients' internet blogs - Robinson Ian; Shah Syed (BMC, 2011)
Abstract Background Patients on oral anticoagulant therapy (OAT) require regular testing of the prothrombin time (PT) and the international normalised ratio (INR) to monitor their blood coagulation level to avoid complications of either over or under coagulation. PT/INR can be tested by a healthcare professional or by the patient. The latter mode of the testing is known as patient self-testing or home testing. The objective of this study was to elicit patients' perspectives and experiences regarding PT/INR self-testing using portable coagulometer devices. Methods Internet blog text mining was used to collect 246 blog postings by 108 patients, mainly from the USA and the UK. The content of these qualitative data were analysed using XSight and NVivo software packages. Results The key themes in relation to self-testing of OAT identified were as follows: Patient benefits reported were time saved, personal control, choice, travel reduction, cheaper testing, and peace of mind. Equipment issues included high costs, reliability, quality, and learning how to use the device. PT/INR issues focused on the frequency of testing, INR fluctuations and individual target (therapeutic) INR level. Other themes noted were INR testing at laboratories, the interactions with healthcare professionals in managing and testing OAT and insurance companies' involvement in acquiring the self-testing equipment. Social issues included the pain and stress of taking and testing for OAT. Conclusions Patients' blogs on PT/INR testing provide insightful information that can help in understanding the nature of the experiences and perspectives of patients on self-testing of OAT. The themes identified in this paper highlight the substantial complexities involved in self-testing programmes in the healthcare system. Thus, the issues elicited in this study are very valuable for all stakeholders involved in developing effective self-testing strategies in healthcare that are gaining considerable current momentum particularly for patients with chronic illness.